Colloidal synthesis of lead-free all-inorganic cesium bismuth bromide perovskite nanoplatelets. Issue 46 (22nd October 2018) - Lian, Linyuan; Zhai, Guangmei; Cheng, Feng; Xia, Yong; Zheng, Moyan; Ke, Jiangping; Gao, Mingyang; Liu, Huan; Zhang, Daoli; Li, Luying; Gao, Jianbo; Tang, Jiang; et al.
Abstract : Lead halide two-dimensional (2D) nanoplatelets (NPLs) have attracted intense interest due to their unique optoelectronic properties. Abstract : Lead halide two-dimensional (2D) nanoplatelets (NPLs) have attracted intense interest due to their unique optoelectronic properties. However, environmental friendly lead-free 2D perovskite NPLs are highly desirable in terms of application. Herein, all-inorganic Cs3 Bi2 Br9 perovskite NPLs are synthesized for the first time via the hot injection method. The Cs3 Bi2 Br9 NPLs are parallelogram-shaped and exhibit an extremely sharp first exciton peak which blue-shifts substantially with respect to their bulk bandgap. The formation of Cs3 Bi2 Br9 NPLs is determined by the layered feature of Cs3 Bi2 Br9 crystalline structure and the shape of parallelogram is the reflection of the trigonal nature of Cs3 Bi2 Br9 crystal. The large blue-shift and extremely sharp first exciton peak are due to large exciton binding energy and quantum confinement in the Cs3 Bi2 Br9 NPLs and large exciton binding energy in Cs3 Bi2 Br9 crystal. The Cs3 Bi2 Br9 NPLs grow anisotropically from monodispersed parallelogram-shaped nuclei via Ostwald ripening, demonstrated by ex situ TEM investigation. Anion-exchange was used to effectively adjust the composition of the Cs3 Bi2 Br9 NPLs. Additionally, the Cs3 Bi2 Br9 NPLs exhibit excellent stability to air and illumination due to the robust crystal, BiOBr passivation and oleylamine and oleic acid co-passivation.